Relevansi Nilai Moral dalam Antologi Cerpen Pacar Seorang Seniman Karya W. S. Rendra pada Pembelajaran Sastra (MARDIBASA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2022)
This article aims to explain the moral aspect in the short story anthology of Pacar Seorang Seniman by W. S. Rendra. This research uses short stories in the anthology of Pacar Seorang Seniman by W. S. Rendra using an analytic descriptive method with a qualitative approach. A pragmatic approach is used to deep review Rendra's 186-pages anthology which was published in its first printing, October 2016. The data collection used in this research is the reading and note-taking technique. The results of the study show that in this anthology there are moral values related to oneself, moral values among humans, humans and God, and humans and nature. Many moral values are conveyed by the author in the collection of Pacar Seorang Seniman short stories, either through the author's description or dialogue between the characters. This is applied as a means for cultivating the noble characters as stated in the 2013 Curriculum. The short story collections of Pacar Seorang Seniman has met the criteria for literary appreciation materials so that it is appropriate to be used as the appreciation materials for learning prose at the high school level, that is the analyzing values in literary works.